A comprehensive fault location estimation using voltage sag profile for non-homogenous distribution networks - Mokhlis, Hazlie; Li, H.Y.; Mohamad, H.; Bakar, A.H.A. (Praise Worthy Prize, 2010)
An improvement in service continuity of power supply in distribution system could be achieved through a fast jault location. In line with this objective, a fault location method for a distribution network is proposed in this paper. The method uses non-linear voltage sag profile equations as a means to locate a fault. Considering the possibility of having non-homogeneity of line impedances in distribution network, the voltage sag profile equations are constructed for each section. The possible fault location is estimated by incorporating the measured voltage magnitude and its corresponding phase angle into equation of voltage sag as a function of fault distance. The uncertainty of fault resistance is also considered in this method by constructing the voltage sag equations bayed on different fault resistance values. The performance of the algorithm is presented using an actual distribution network.